Financial Technology and MSME Sustainability: The Mediating Role of Financial Literacy, Financial Inclusion, and Moderating Government Support - Heri Mahyuzar; Awaludin Abid; Candra Prawira Budi Pamungkas (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2026)
This study examines how financial technology contributes to MSME sustainability by analyzing the mediating roles of financial literacy and financial inclusion and the moderating role of government support. While prior studies have largely emphasized the direct link between fintech adoption and MSME performance, less attention has been given to the capability-based and institutional mechanisms through which fintech generates sustainable outcomes. Drawing on Resource-Based Theory and Social Network Theory, this study applies an explanatory sequential mixed-method design by combining PLS-SEM analysis of survey data from 350 MSME actors in Kebumen, Surakarta, and Semarang with NVivo-based thematic analysis of semi-structured interviews. The findings reveal that fintech supports MSME sustainability primarily by strengthening financial literacy and financial inclusion, with financial literacy emerging as the more decisive mechanism for transforming digital financial use into sustainable business capability. However, government support does not significantly strengthen the effects of financial literacy and financial inclusion on sustainability, indicating that institutional assistance may remain ineffective when access is uneven, administratively complex, and poorly aligned with MSME needs. Theoretically, this study extends Resource-Based Theory by positioning financial literacy as a key capability that converts fintech and financial access into sustainability outcomes, while refining Social Network Theory by showing that external institutional support creates value only when it is accessible, relevant, and operationally aligned. Methodologically, the study contributes by integrating PLS-SEM and NVivo-based qualitative analysis to explain both statistical relationships and contextual mechanisms. The findings imply that MSME policy should move beyond general fintech adoption and financial access programs toward targeted digital financial literacy, productive financial inclusion, and need-based government support.